Cytochrome P450 expression patterns in human osteoblasts during osteogenic differentiation with or without TNFα treatment. (12th May 2020) - Pathak, Janak L.; Liu, Lingyu; Zhu, Yong‐qiang; Bureik, Matthias
Abstract: Background: Recently the expression patterns of several cytochrome P450 (CYP) genes in different human osteoblast models were reported. However, the various expression patterns of CYPs in human osteoblasts during different stages of osteogenic differentiation have not been investigated and the effect of inflammatory cytokines on CYPs expression in osteoblasts is unknown. Methods: The expression levels of nine different CYP genes in the human osteoblast cell line MG63 and in primary human osteoblasts (HOB) during osteogenic differentiation with or without treatment with tumor necrosis factor‐α (TNFα) were analyzed by quantitative real‐time PCR. Results: The expression levels of most CYPs under study show a significant time dependence during osteogenic differentiation. Overall, more highly significant CYP expression level changes occur in HOB than in MG63 cells. Treatment with TNFα causes a variety of CYP expression level changes in both HOB and MG63 cells. Conclusions: Our findings indicate that TNFα treatment reduces steroid hormone production in MG63 cells (but not in HOB) at the level of lanosterol‐demethylation during cholesterol biosynthesis. By contrast, TNFα treatment of HOB cells (but not in MG63) leads to the upregulation of several key enzymes involved in the biosynthesis of sex steroids, which is proposed to lead to higher levels of estrogen production. These data also suggest that at least with respect to the topic of this study the cell line MG63 is not a good representative for osteoblasts and that it is preferential to use primary osteoblasts instead.